2012
DOI: 10.4161/cc.21790
|View full text |Cite
|
Sign up to set email alerts
|

Human telomerase reverse transcriptase (hTERT) is a target gene of β-catenin in human colorectal tumors

Abstract: (2012) Human telomerase reverse transcriptase (hTERT) is a target gene of β-catenin in human colorectal tumors, Cell Cycle, 11:17,[3331][3332][3333][3334][3335][3336][3337][3338]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Recent reports identified a direct link between the Wnt/β-catenin signaling pathway and hTERT expression in normal embryonic and adult stem cells and cancer cells [42], [43], [44]. Interestingly, our data demonstrate that there is a context-dependent regulation of the hTERT promoter by the HH/GLI signaling pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Recent reports identified a direct link between the Wnt/β-catenin signaling pathway and hTERT expression in normal embryonic and adult stem cells and cancer cells [42], [43], [44]. Interestingly, our data demonstrate that there is a context-dependent regulation of the hTERT promoter by the HH/GLI signaling pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore whole RNA was isolated from microdissected tumor areas using RNeasy kits (Qiagen; 74404) as previously described [24]. RNA concentrations were measured by UV-photometry.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies concluded that telomerase played a key role in regulating cell proliferation which is associated with various disorders (e.g. endometriosis and colorectal cancer) [29][30][31][32]. In fact, Wnt/β-catenin has been documented to exacerbate cell proliferation by binding with the T-cell factor (TCF)/ lymphoid-enhancing factor (LEF) family and inducing some oncogene expressions including C-myc and cyclin D1(CCND1) [33].…”
Section: Discussionmentioning
confidence: 99%